Pengembangan Media Edukasi Diriku untuk Mengatasi Masalah Pubertas Siswi Madrasah Ibtidaiyah Al Ma'arif 03 Langlang Singosari - Putri, Rona Sari Mahaji; Sari, Nila Kartika (Jurnal Akademika Baiturrahim Jambi, 2025)
Many adolescent girls (female students) are not ready and do not understand what happens when entering puberty. Puberty is one of the periods that a person goes through before adolescence. Various changes occur, but are often not understood by adolescents. Lack of knowledge will have an impact on the attitudes and behavior of early adolescents in responding to various things during puberty. Sexual education during puberty is often considered taboo by adolescents, so it tends to be less noticed and discussed. It takes a health education that is easy for adolescents to understand, acceptable and unconsciously provides benefits for adolescents. The purpose of the research is to make educational media "Myself at Puberty (Female Series)" for madrasa students, which makes it easier for students to understand about puberty. This research is a development research, which will be applied to elementary school children (SD) grades 4-6 at Madrasah Ibtidaiyah Al Ma'arif 03 Langlang Singosari. The instrument uses a comic book that has been made by the research team. This research variable is the development of educational media. Data collection was carried out through observation (student response), interviews and questionnaires. The form of education was packaged through counseling with comic media. Data were analyzed quantitatively, presented through frequency distribution. The results showed that educational media in the form of the book "Myself During Puberty" was effective in providing students with an understanding of puberty. The feasibility of the book is rated 100% and feasible as learning media, based on validation assessments from media experts and material experts.